The impact of social responsibility in marketing on customers satisfaction to Mobilis Mobile service in the city of Constantine - Brahimi, Massika; Merdaoui, Kamel (Journal of Human Sciences, 2020)
This study is an attempt to analyse the impact of corporate social responsibility in marketing on customers’ satisfaction through its main dimensions, namely, the responsibility towards consumer, the responsibility towards society, and the responsibility towards environment.In order to achieve the purpose of this study, a random sample of 140 customers of Mobilis.  towards which a constructed questionnaire was handed. 120 questionnaires were collected and analysed by using the Statistical Package of Social Sciences (SPSS). It is found out from the empirical study that even though Mobilis Company is socially responsible in marketing, its customers are undifferentiated. They are enable to construct a clear understanding of the company’s efforts towards this emerging philosophy.